2014
DOI: 10.1021/la501008x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ion Effects on the Self-Assembly of Ionic Surfactants: A Molecular Thermodynamic Theory of Micellization with Dispersion Forces

Abstract: The self-assembly of amphiphilic molecules is a key process in numerous biological and chemical systems. When salts are present, the formation and properties of molecular aggregates can be altered dramatically by the specific types of ions in the electrolyte solution. We present a molecular thermodynamic model for the micellization of ionic surfactants that incorporates quantum dispersion forces to account for specific ion effects explicitly through ionic polarizabilities and sizes. We assume that counterions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 55 publications
4
60
0
Order By: Relevance
“…According to Collins' concept of matching water affinities [24][25][26][27], soft headgroups should come in close contact with soft counterions, thus the soft alkyl sulfonate should come in close contact with soft counterions like Rb + whereas hard counterions like Na + remain further away. The calculated counterion distribution profiles by the molecular thermodynamic theory of micellization with dispersion forces [60] are in line with Collins's concept of matching water affinities. The theory calculation results illustrate that K + and Cs + can get very close to the SDS micelle surface and reach all the way to the surface of charge, whereas Li + and Na + have a distance of closest approach, slightly closer for Na + and slightly further from the micelle surface for Li + .…”
Section: Micellization Of Pure Ionic Surfactantssupporting
confidence: 81%
See 1 more Smart Citation
“…According to Collins' concept of matching water affinities [24][25][26][27], soft headgroups should come in close contact with soft counterions, thus the soft alkyl sulfonate should come in close contact with soft counterions like Rb + whereas hard counterions like Na + remain further away. The calculated counterion distribution profiles by the molecular thermodynamic theory of micellization with dispersion forces [60] are in line with Collins's concept of matching water affinities. The theory calculation results illustrate that K + and Cs + can get very close to the SDS micelle surface and reach all the way to the surface of charge, whereas Li + and Na + have a distance of closest approach, slightly closer for Na + and slightly further from the micelle surface for Li + .…”
Section: Micellization Of Pure Ionic Surfactantssupporting
confidence: 81%
“…6A) due to their higher degree of matching water affinities, while hard Na + cations and soft Br − anions cannot form strong ion pairs, the hard/soft ion pairs are always separated by water (Fig. 6B) [60]. The formation ability of ion pairs between Br − anions and Y + cations enhances according to the following sequence: Na + < K + < Rb + .…”
Section: Mixed Micellization Of 12mentioning
confidence: 96%
“…In contrast, for classical ionic surfactants, the counterions decrease both CAC and micellar size according to the Hofmeister series. [30][31][32] Nevertheless, highly hydrated small cations (Li + and H 3 O + ) are more prone to condense onto COSAN aggregates as compared to Na + and K + , which is in line with the Hofmeister series.…”
Section: Potential Of Mean Force Of Cosansupporting
confidence: 59%
“…18,33,38 By doubling the initial ratio of the amount of chloroform to the total aqueous fraction typically used in the MB detergent assay, we did not require extensive backwashing to eliminate interference from potential contaminating ions or compounds. 19,39 We also found that we were able to scale down the entire assay to mL amounts by using a detergent:MB solution ratio of 1:100 for SDC and 1:1000 for SDS, respectively, and that we could generate linear curves for the entire potential anionic detergent concentration range used in most lung decellularization schemes.…”
Section: Discussionmentioning
confidence: 85%